Secondary malignancies in chronic myeloid leukemia patients after imatinib-based treatment: long-term observation in CML Study IV - Miranda, M. B.; Lauseker, M.; Kraus, M-P; Proetel, U.; Hanfstein, B.; Fabarius, A.; Baerlocher, G. M.; Heim, D.; Hossfeld, D. K.; Kolb, H-J; Krause, Stefan; Nerl, C.; et al. (Leukemia, 2016)
Treatment of chronic myeloid leukemia (CML) has been profoundly improved by the introduction of tyrosine kinase inhibitors (TKIs). Long-term survival with imatinib is excellent with a 8-year survival rate of 88%. Long-term toxicity of TKI treatment, especially carcinogenicity, has become a concern. We analyzed data of the CML study IV for the development of secondary malignancies. In total, 67 secondary malignancies were found in 64 of 1525 CML patients in chronic phase treated with TKI (n=61) and interferon-? only (n=3). The most common malignancies (n?4) were prostate, colorectal and lung cancer, non-Hodgkin's lymphoma (NHL), malignant melanoma, non-melanoma skin tumors and breast cancer. The standardized incidence ratio (SIR) for all malignancies excluding non-melanoma skin tumors was 0.88 (95% confidence interval (0.63-1.20)) for men and 1.06 (95% CI 0.69-1.55) for women. SIRs were between 0.49 (95% CI 0.13-1.34) for colorectal cancer in men and 4.29 (95% CI 1.09-11.66) for NHL in women. The SIR for NHL was significantly increased for men and women. An increase in the incidence of secondary malignancies could not be ascertained. The increased SIR for NHL has to be considered and long-term follow-up of CML patients is warranted, as the rate of secondary malignancies may increase over time.
EVALuna2:25736